Supply base management : an empirical investigation - Goffin, Keith; Szwejczewski, Marek; New, Colin (Cranfield University, 1996)
Manufacturing companies place a strong emphasis on the role of supply chain management-the management of supplies, suppliers, inventory and distribution. Supplier management is key and much of the literature talks about the trend to reduce supplier base. Database analysis gave empirical evidence of this trend in UK manufacturing companies-201 companies from different industrial sectors were all found to have cut their supplier base over the last four years, on average by 9% in the household products sector and approximately 35% in the process, engineering and electronics sectors. Further research at four companies looked at their experiences with suppliers and established that a key reason for supplier base reduction is to free time to more effectively manage the remaining suppliers. The criteria used for supplier selection and reasons why single- sourcing was avoided were also identified. These findings on supplier management have implications for both researchers and managers in industry.
Keywords: UK manufacturing; Supply chain management; supplier base and supplier relationships